High protein and iron-folate crackers supplementation on the iron status of pregnant women (Faculty of Medicine Universitas Indonesia, 2003)
Previous studies have revealed that several factors influenced the relatively low success of iron supplementation for pregnant women. The factors included poor distribution, low coverage and compliance, as well as low absorption. The aim of this study is to measure the iron status of pregnant women after consuming crackers containing fish powder and iron-folate. This study was carried out in the Purworejo district (Central Java) from February through October 2002. Using a randomized controlled trial (RCT) design, 70 pregnant women in their second-third month of pregnancy were recruited, and divided into two groups. Ten women dropped out during the study. The first group consisted of 28 women were given protein – iron enriched crackers (PIEC group), while the second group of 32 women were given iron–enriched crackers (IEC group) for a total of 12 weeks. The results showed that the hemoglobin (Hb) levels and serum transferrin receptors (sTfR) of both groups were increased. Serum ferritins (SF) of both groups were decreased. At the end of the study, the increase in Hb and sTfR levels between the two groups were significantly different, while the decrease in SF was not significantly different. Animal protein from fish powder tended to improve absorption of non-heme iron among pregnant women, resulting in improved Hb and sTfR levels. (Med J Indones 2003; 12: 243-6)